Peer review of the pesticide risk assessment of the active substance zoxamide. (25th September 2017) - ,; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Bellisai, Giulia; Brancato, Alba; Brocca, Daniela; Bura, Laszlo; Byers, Harry; Chiusolo, Arianna; Court Marques, Daniele; Crivellente, Federica; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Latvia, and co‐rapporteur Member State, France, for the pesticide active substance zoxamide are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of zoxamide as a fungicide on wine and table grapes, and potatoes. The reliable end points, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.